Analysis of Slang Language in The “Full Senyum” Community on X and Implications - Natalia, Iis; Aceng Hasani; Ilmi Solihat (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This research is motivated by the tendency of teenagers to use slang language on social media X, leading to the emergence of new vocabulary. The use of slang on social media ultimately results in a low understanding of formal language, correct language structures, and misinterpretation of meanings. Therefore, the purpose of this study is to describe the forms and meanings of slang vocabulary within the Full Senyum Community on X. The method used in this study is descriptive qualitative, employing observation, note-taking, and documentation techniques for data collection. The results of the data analysis reveal five forms of slang vocabulary: basic word forms, derived word forms, acronym forms, abbreviation forms, and reduplication forms. In addition to these forms, the analysis also identifies four types of slang word meanings: general meanings, reduction meanings, denotative meanings, and connotative meanings. The findings of this research have implications for Indonesian language learning in high schools. It emphasizes the need for a pedagogical approach that integrates the phenomenon of slang to enhance students' linguistic awareness and their formal and informal language skills. Furthermore, incorporating slang language as teaching material can make learning more engaging and relevant to students' lives.